Brighton rock - Greene, Graham, 1904- (London : Vintage Books, 2004)
Reprint of Graham Greene's 1938 novel about Pinkie, a young man who overreaches himself in pursuit of his criminal ambitions in the underworld of Brighton.
Adult
Keywords: Criminals -- England -- Brighton -- Fiction; Young men -- England -- Brighton -- Fiction; Criminals -- Fiction; Young men -- Fiction; Brighton (England) -- Fiction; Brighton (England) -- Fiction; Psychological fiction